APPROPRIATION OF LAND FOR STATE AND MUNICIPAL NEEDS IN THE EU COUNTRIES AND IN UKRAINE - Kozlova, Tetiana; Rudich, Oleksij (Proceedings of National Aviation University (archive), 2015)
The article is devoted to the appropriation of land in the EU and Ukraine. We identify the main features and differences of land appropriation for public use in the EU and in Ukraine and analyze the problems that can occur with improper appropriation. The paper represents comparative analysis of land appropriation procedures in Ukraine and in the EU.